The Relationship Between Halitosis and Anxiety in Medical Students Faculty of Medicine at Universitas Katolik Atma Jaya - Latumahina, Cleo Michaela; Oktaria, Indriani; Lonah (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Halitosis is a common occurrence among people. Halitosis can be classified as genuine halitosis, where the sufferer genuinely has bad breath that can be smelled by people around them, or as delusional halitosis, where the sufferer believes that they have bad breath but it cannot be smelled by people around them. Halitosis can become a significant problem, especially when the sufferer is socializing with others, due to the anxiety that their bad breath might disturb their conversation partners. This condition can lead to poor communication skills and actions of isolation or withdrawal from others. Material & methods: This study seeks to explore the perceptions and knowledge of medical students at Universitas Katolik Atma Jaya about halitosis, as well as its impact on their anxiety levels. Utilizing a cross-sectional design, the research involved 150 students from the Faculty of Medicine and Health Sciences, class of 2020–2022. Halitosis, as the independent variable, was assessed using the Halitosis Consequences Inventory (ICH), while anxiety, the dependent variable, was measured through the Depression Anxiety Stress Scale (DASS-42). Data analysis was conducted using the Spearman Rank Correlation Coefficient test. Results: Results of the research are 34.7% of Faculty of Medicine at Universitas Katolik Atma Jaya’s students from the class 2020-2022 experience halitosis, while 65.3% experience anxiety. 76.9% of students with halitosis also experience anxiety. The results of the Spearman Rank Correlation Coefficient test indicate a weak positive correlation (rs = 0.321) that is statistically significant (p = 0.000) between halitosis and anxiety. In other words, there is a tendency that an increase in halitosis will affect the increase in anxiety levels. Conclusion Relation between halitosis and anxiety is a synergy (positive correlation). Halitosis has a moderate positive influence on anxiety among the students of the Faculty of Medicine at Universitas Katolik Atma Jaya, class of 2020. This indicates that students experiencing halitosis are concerned about their bad breath, which affects their social communication. Therefore, the approach to treating halitosis should include both physical treatment (halitosis) and mental health care.